Effects of Feeding Increasing Levels of HP 300 on Nursery Pig Performance - A. M. Jones; J. M. DeRouchey; G. Fitzner; J. C. Woodworth; M. D. Tokach; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,215 pigs (PIC 337 × 1050; initial BW 11.3 lb) were used in a 43-d growth trial evaluating the effects of feeding increasing HP 300 (Hamlet Protein, Findlay, OH) on nursery pig performance. Pigs were weaned at 16 to 19 d of age and placed in pens, with each pen containing a mix of barrows and gilts. Pens of pigs were weighed and allotted by BW to 1 of 5 dietary treatments in a randomized complete block design with 27 pigs per pen and 9 pens per treatment. The control diet was a standard cornsoybean meal-based diet with 7.5 and 5.63% fish meal (FM) included in phases 1 and 2, respectively. First, the diet with the highest inclusion of HP 300 (phase 1 – 20%; phase 2 – 15%) was formulated and 2 intermediate diets (low and medium HP 300) were then created to have an equal stepwise increase in HP 300 with the HP 300 included at the expense of soybean meal and fish meal. A fifth treatment was then formulated to have the same amount of soybean meal as the control diet, with HP 300 replacing fish meal. From d 22 to 43, a common phase 3 diet was fed to all pigs. Phase 1 diets were fed in pellet form, while phases 2 and 3 were fed in meal form. From d 0 to 7 (phase 1), increasing HP 300 at the expense of soybean meal and fish meal decreased ADFI (quadratic, P = 0.001) in pigs fed the low HP 300 diet, but then increased as HP 300 was increased. No differences were observed for ADG or F/G. Furthermore, performance did not differ between pigs fed the fish meal control diet and pigs fed the diet with HP 300 replacing fish meal. During phase 2 (d 7 to 22), ADG and ADFI decreased (linear, P<0.05) as HP 300 increased at the expense of soybean meal and fish meal resulting in a tendency for poorer F/G (quadratic, P = 0.073). However, no differences were observed between pigs fed the fish meal control diet and pigs fed HP 300 replacing fish meal. For the entire period when the specialty protein sources were fed (d 0 to 22), pigs fed increasing HP 300 had poorer ADG, ADFI, and final BW (linear, P<0.05) as HP 300 increased, but there were no differences observed for F/G. In addition, there were no differences observed between pigs fed the fish meal control diet and pigs fed the HP 300 diet replacing fish meal. From d 22 to 43 (phase 3) when a common diet was fed, F/G tended (quadratic, P = 0.075) to improve as HP 300 increased in the previous diets with pigs previously fed the diet with the low inclusion of HP 300 having the best F/G. Overall (d 0 to 43), pigs fed increasing HP 300 had a tendency for poorer ADFI (linear, P = 0.071) resulting in a decreased final BW (linear, P = 0.043). However, no differences were observed for growth performance between pigs fed the fish meal control diet and pigs fed HP 300 replacing fish meal. For the economic analysis, feed cost per pig and cost per pound of gain decreased (linear, P<0.05) for pigs fed increasing HP 300. However, there were no differences detected for revenue per pig and income over feed cost. In conclusion, increasing HP 300 up to 15 to 20% of the diet for the first 22 d post-weaning at the expense of soybean meal and fish meal resulted in a decrease in final BW at the end of the nursery period.
Keywords: growth; fish meal; HP 300; nursery pig